AN ANALYSIS OF STUDENTS' READING COMPREHENSION SKILLS IN UNDERSTANDING NARATIVE TEXTS IN SMP N 7 MEDAN - rajainan simanjorang; Nazla Humaira; Natalia Widya Pasca Tarigan (ELT (English Language Teaching Prima Journal), 2024)
This study was conducted to describe students' ability in understanding narrative text and the factors that influence it. The purpose of this study is toanalyze students' ability to understand narrative text and the factors that influence it. This research method used descriptive qualitative method. This research was conducted at SMP N 7 Medan. The subjects of this study were 30 students of class IX-6. This research used question answering test and interview test instruments. Based on the results of the study, it was found that the average comprehension ability of narrative text was 82.33 (high ability), then from the data it was also found that the factor that most influenced students' reading comprehension ability at SMP N 7 Medan was the word meaning factor with a percentage of 29.54% out of 100%, followed by vocabulary 27.27%, grammar 25% and linguistic factors 18.18%. The main cause is the limited vocabulary owned by the students.Keywords: Reading, Narrative text, influencing factors, Ability Analysis